Fiat 4-Stroke Engine Performance Test With 1100 Cc Capacity Using Automotive Engine Test Bed T101d - Dian Wahyu (Jurnal Teknik Mesin (JTM), 2019)
Engine is the main power in the vehicle and has a different performance. The differences in engine performance can occur due to different operating conditions and the fuel used. Therefore, research on the performance of combustion engines must be done to improve service to consumers, because not everyone can perform performance engine performance tests. At the time of planning the manufacture of the combustion engine, theoretical performance was calculated, but the results were different from the actual performance results on the dynamometer. Therefore an engine is tested for performance tests to get the characteristic value of the engine. The process of testing has been carried out in accordance with the Standard Operation Procedure in the relevant literature and concludes that the performance produced by the test machine shows the value of torque characteristics, the average effective pressure of the combustion chamber, fuel consumption and volumetric efficiency which is inversely proportional to the engine rotation speed . For the optimal variable engine operating conditions in this study were at 4000 Rpm with 72 Nm of torque and 30.1 Kw of power with a specific fuel consumption of 311.5 g / kWh